Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Fang Yi-ping; Zhu Fu-biao; Yi Shu-hua; Qiu Xiao-ping; Ding Yong-jian (Journal of Mountain Science, 2019)
Permafrost is one of the key components of terrestrial ecosystem in cold regions. In the context of climate change, few studies have investigated resilience of social ecological system (SER) from the perspective of permafrost that restricts the hydrothermal condition of alpine grassland ecosystem. In this paper, based on the structural dynamics, we developed the numerical model for the SER in the permafrost regions of the source of Yangtze and Yellow Rivers, analyzed the spatial-temporal characteristics and sensitivity of the SER, and estimated the effect of permafrost change on the SER. The results indicate that: 1) the SER has an increasing trend, especially after 1997, which is the joint effect of precipitation, temperature, NPP and ecological conservation projects; 2) the SER shows the spatial feature of high in southeast and low in northwest, which is consistent with the variation trends of high southeast and low northwest for the precipitation, temperature and NPP, and low southeast and high northwest for the altitude; 3) the high sensitive regions of SER to the permafrost change have gradually transited from the island distribution to zonal and planar distribution since 1980, moreover, the sensitive degree has gradually reduced; relatively, the sensitivity has high value in the north and south, and low value in the south and east; 4) the thickness of permafrost active layer shows a highly negative correlation with the SER. The contribution rate of permafrost change to the SER is -4.3%, that is, once the thickness of permafrost active layer increases 1 unit, the SER would decrease 0.04 units.